Effect of enzyme-response Mag@CMCS@CPSG film on rice sheath blight disease (caused by Rhizoctonia solani) control and rice quality - Mo, Feixu; Long, Youhua; Li, Ming; Ding, Yi; Wu, Shuai; Li, Rongyu (Frontiers in Sustainable Food Systems, 2023)
To find a precise, efficient, and safe method to control rice sheath blight disease (caused by Rhizoctonia solani), this study used the natural product magnolol as the fungicide. Based on the characteristics of cell wall-degrading enzymes (CWDEs) released by R. solani during the early stages of infection, a Mag@CMCS@CPSG (magnolol@carboxymethyl chitosan@carboxymethyl cellulose, pectin, sodium alginate, and glycerol) film was constructed to control the release of magnolol in response to CWDEs. The Mag@CMCS@CPSG film increased magnolol toxicity against R. solani, decreased EC50 from 7.33 μg/mL to 4.37 μg/mL, and effectively blocked the invasion of mycelia. Under the stimulation of CWDEs released during R. solani infection, the cumulative release of magnolol by the Mag@CMCS@CPSG film reached 75.62% after 96 h, and the disease index of rice treated with Mag@CMCS@CPSG film significantly decreased. The maximum field control effect of Mag@CMCS@CPSG film on rice sheath blight disease was 72.47%, which was not significantly different from that of the commercial preparation jinggangmycin; however, the holding period was better. The Mag@CMCS@CPSG film reduced the loss of rice yield and quality caused by infection with R. solani and did not cause phytotoxicity or residue. In conclusion, the Mag@CMCS@CPSG film can achieve accurate and green control of rice sheath blight.